Generation of an induced pluripotent stem cell (iPSC) line carrying a KCNA2 homozygous (p.Arg294His, R294H) mutation related to hereditary spastic paraplegia - Hang Lyu; Carolin Haag; Niklas Schwarz; Heidi Löffler; Ulrike A. Mau-Holzmann; Holger Lerche; Filip Rosa (Stem Cell Research)
The KCNA2 gene encodes the voltage-gated potassium channel Kv1.2, which is essential for repolarization of action potential. The R294H variant in KCNA2 represents the only potassium channel gene variant linked to hereditary spastic paraplegia (HSP) to date. However, this variant has been observed exclusively in heterozygous individuals. Here, we generated a homozygous KCNA2 R294H (c.881G > A) induced pluripotent stem cell (iPSC) line from a healthy individual iPSC line. The variant was introduced into both alleles using the CRISPR/Cas9 system. The resulting iPSC line has a normal karyotype, expresses key pluripotency markers, and is able to differentiate into all three germ layers.